PENGEMBANGAN METODOLOGI PEMBELAJARAN PAI: IMPLEMENTASI QUANTUM TEACHING DI SMPN KOTA BENGKULU - Alfauzan Amin (Ta'dib: Jurnal Pendidikan Islam, 2011)
AbstractThis study aims to describe: 1) The perception of teachers in the development of Islamic learning methodology by implementing Quantum Teaching in junior high school in Bengkulu 2) Development of Islamic learning methodologies by implementing Quantum Teaching in junior high school in Bengkulu. 3) factors supporting or inhibiting the implementation of religious teachers in the development of Islamic learning methodology by implementing Quantum Teaching in junior high school in Bengkulu. In line with the nature of the research, the research method used is qualitative method. Bogdan and Taylor (in Moeleong, 1996) defines "qualitative method" as a research procedure that produces descriptive data in the form of words; written or spoken by people and the observed behavior. According to him, this research is directed at the background of the individual in a holistic (whole). Application of Quantum Teaching in the development of PAI learning methodologies is an interesting learning model conducted among teachers, students and schools in together to reach peak performance. Perception is what has been owned by religious teachers in most of the city of Bengkulu on the SMP. Therefore, a religious teacher in junior high trying to apply Quantum Teaching is a must. Being a Quantum teacher that will make the grade "Passionate and Joyful" needs to support all elements. This is evident from the Adabiyah teachers who do not understand the concept of Quantum Teaching in depth. The existence of several techniques for applying the principles of Quantum Teaching is incompatibilities with the culture, habits and the potential of the environment with the power of creativity; teachers can make use of existing facilities. Keyword: learning, Quantum Teaching